THE RELATIONSHIP BETWEEN DIET AND PHYSICAL ACTIVITY IN THE ELDERLY WITH CHOLESTEROL IN INDRA JAYA SUB-DISTRICT, ACEH JAYA DISTRICT IN 2023 - Hidayattullah, Mhd.; Khaira, Ulfa (Transpublika Publisher, 2023)
The aging process is a continuous series of bodily modifications that can impair the body's cholesterol-regulating functions. This study aimed to determine if there's a correlation between dietary habits and increasing cholesterol levels among the elderly population in Indra Jaya sub-district. Employing a cross-sectional survey design, researchers collected data from elderly residents in Tengela village through questionnaires. The findings indicate a strong association between consuming fruits and vegetables and maintaining healthy cholesterol levels in the majority (93.5%) of participants. Statistical analysis confirmed a significant relationship between dietary patterns, physical activity, and cholesterol levels in this elderly group. Further analysis delved into the frequency and distribution of these factors. Essentially, this research suggests that dietary choices play a crucial role in cholesterol management for the elderly.